Pengembangan Video Pembelajaran Berbasis ICARE (Introduction, Connection, Application, Reflection, dan Extension) untuk Meningkatkan Hasil Belajar Siswa Kelas VIII di SMP N 2 Sungai Tarab - Febrida Rahmatil Ulya; Ika Metiza Maris (Edusainstika: Jurnal Pembelajaran MIPA, 2022)
This study departs from student learning at school, namely the lack of awareness of students in participating in mathematics learning and the lack of student involvement in learning. The various characteristics of students make many students who do not understand the material from learning mathematics. When learning online, students only receive learning through LKPD, without explanation by the teacher. Students prefer the material in mathematics learning they can see and they visit. The purpose of this research is to produce a valid, practical, and effective ICARE-based learning video. This study uses development research methods. This research consists of 3 stages, namely the definition stage, the design stage, and the development stage. The definition stage is carried out to define the needs in the learning process and collect various information related to the product to be developed. Furthermore, the design stage aims to design learning videos. The last stage of development is to develop learning videos that have been designed that are valid, practical, and effective. The results showed that the designed learning video was valid with a validation result of 78.45%. Then the ICARE-based learning videos have been practically used with the practical results of 16 students of class VIII SMP N 2 Sungai Tarab amounting to 61.175%. In addition, ICARE-based learning videos have been effectively used based on students' responses to learning, namely students where the percentage is 81.4%. Student learning outcomes increased with the N-Gain category of 0.67% with sufficient criteria.